Non-swellable, cytocompatible pHEMA-alginate hydrogels with high stiffness and toughness - Kim, Yong-Woo; Kim, Ji Eun; Jung, Youngmee; Sun, Jeong-Yun (Elsevier BV, 2019)
Human skin exhibits high stiffness of up to 100 MPa and high toughness of up to 3600 J m(-2) despite its high water content of 40-70 wt%. Engineering hydrogels have rarely possessed both high stiffness and toughness, because compliant hydrogels usually become brittle when excess crosslinker is added to make the gel stiff. Furthermore, conventional hydrogels usually swell under physiological conditions, weakening their mechanical properties. Here, we designed a non-swellable hydrogel with high stiffness and toughness by interpenetrating covalently and ionically crosslinked networks. The stiffness is enhanced by utilizing ionic crosslinking sites fully, and the toughness is enhanced by adopting synergistic effects between energy-dissipation by ionic networks and crack-bridging by covalent networks. Non-swelling behaviors of the gel are achieved by densifying covalent and ionic crosslinks. The hybrid gel shows high elastic moduli (up to 108 MPa) and high fracture energies (up to 8850 J m(-2)). In vitro and in vivo swelling tests prove non-swelling behaviors of the gel. Live/dead assays show 99% cell viability over a period of 60 days.
Keywords: POLY(2-HYDROXYETHYL METHACRYLATE); NETWORKS; BEHAVIOR